Implementasi Walking Exercise dalam Menurunkan Tekanan Sistole dan Diastole Penderita Hipertensi - Nur Isriani Najamuddin; M. Syikir; Hadryani Amin; Lisda Alvita; Masyitah Wahab; Andan Firmansyah (Yayasan Inspirasi El Burhani, 2022)
Introduction: Hypertension is a state of increased blood pressure above normal. Hypertension in Indonesia is still a health problem with a high prevalence of 25.8% and there are still 19,559 cases of hypertension in Mamasa Regency. Walking exercise is a form of moderate physical exercise, with the technique of walking regularly for at least 3 times a week with a minimum duration of 20-30 minutes for each exercise. Objective: Treatment of hypertension in clients has been carried out both pharmacologically and non-pharmacologically. We apply one of the non-pharmacological therapies for hypertension, namely walking exercise Method: This community service method is a follow-up activity from research (evidence based practice) and health promotion courses with an approach that uses interviews, blood pressure checks, health promotion and simulation of walking exercise methods for 2 weeks. This community service activity was carried out in April 2021. There were 40 elderly participants who took part in this activity. Results: The results of this community service activity show that the elderly perform the walking exercise method for 3 times per week, and the results of the examination show an average decrease in systolic and diastolic blood pressure in the elderly. Conclusion: The walking exercise method can be used as a non-pharmacological complementary therapy to help reduce blood pressure in the elderly.